Risk management in the shipping industry : a decision tree approach to political risk mitigation in the crude tanker market - Tay, Jin Rong (Nanyang Technological University, 2021)
The relationship between oil and politics has made political risk inherent to businesses involved in the production and transportation of oil. Being one of the main forms of oil transportation, the tanker shipping business has long been exposed to such risks. While such risks can be managed through avoidance and transference via insurance, the complex outcomes of political risk events can make risk management strategies difficult to formulate and implement. As the geopolitical climate of the world changes over time, certain political risk events have also risen in prominence. This paper explores the use of the decision tree model to aid political risk management in tanker shipping at an operational level. The results include quantitative and qualitative estimations of outcomes in response to different risk management strategies under two notable political risk scenarios in the context of today’s tanker shipping market.